1989
DOI: 10.1093/oxfordjournals.aje.a115348
|View full text |Cite
|
Sign up to set email alerts
|

Connective Tissue Disease in Southeastern Georgia: A Case-Control Study of Etiologic Factors

Abstract: The authors conducted a population-based case-control study of connective tissue disease in a four-county area in southeastern Georgia. Interviews with 44 cases and 88 controls were conducted in September and October of 1986. The association with a family history of these disorders was reconfirmed, and a positive association with the use of hair dyes was found. A negative association was found with a family history of diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
5

Year Published

1991
1991
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 0 publications
2
22
0
5
Order By: Relevance
“…We used the matched case-control data set to assess the construct validity of our study design. We tested for associations with a panel of factors documented in prior studies to be associated with SLE, including herpes zoster [6,7,34,35], urticaria [6,9], allergy to sulfonamides [10][11][12], and miscarriage [5]. Our analyses demonstrated associations that were consistent with prior studies and showed strong concordance with respect to effect size.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…We used the matched case-control data set to assess the construct validity of our study design. We tested for associations with a panel of factors documented in prior studies to be associated with SLE, including herpes zoster [6,7,34,35], urticaria [6,9], allergy to sulfonamides [10][11][12], and miscarriage [5]. Our analyses demonstrated associations that were consistent with prior studies and showed strong concordance with respect to effect size.…”
Section: Discussionsupporting
confidence: 58%
“…Participants completed an online questionnaire about demographic factors, medications, comorbidities, common exposures, and a panel of factors consistently associated with SLE (miscarriage [5], shingles [6][7][8], hives [6,9], and allergy to sulfonamides [10][11][12][13]). We used standardized questions derived from previous studies [2,14].…”
Section: The Questionnairementioning
confidence: 99%
“…Those who reported augmentation mammoplasty were asked the year of the procedure, information on the subsequent development of complications, and the year of and indication for explantation, if it occurred. The questionnaire included items from one that had been previously used in a population-based study of factors associated with connective tissue disease (30), with supplementary questions on augmentation mammoplasty that were reviewed by a group of plastic and reconstructive surgeons.…”
Section: Methodsmentioning
confidence: 99%
“…25,26,29 Está bien reconocido el efecto del sexo sobre la susceptibilidad para ciertas enfermedades autoinmunes. En el LES existe un claro efecto de las hormonas sexuales femeninas en el desarrollo y evolución del LES.…”
Section: No3 Mayo-junio De 2002unclassified
“…[25][26][27][28][29][30][31] Tres de estos estudios 26,28,30 tuvieron menos de 100 casos, lo cual limita el poder estadístico, y en otro 26 los casos tenían más de 10 años de evolución, lo cual afecta la calidad de la información evaluada. El objetivo del presente trabajo fue determinar la asociación de factores de riesgo y el desarrollo de LES, con un estudio de casos y controles en población mexicana.…”
Section: Introductionunclassified